"When I go my family will see my life in programmes": Legacy giving and identity at the Royal Opera House. Issue 2 (11th December 2021) - Jones, Marina; Routley, Claire
Abstract: With £5.5 trillion due to be transferred between generations over forthcoming decades in the UK alone, non‐profits stand to increase their income from legacy giving significantly, if they can make lasting and meaningful connections with donors. Extant research suggests that autobiographical memory may play a key role in this process. In this article, we go beyond considering autobiographical memory in general to examining how connection with a particular non‐profit, and the memories that are generated can shape individual identity. We report the results of twenty life‐history interviews with people who plan to leave a legacy to the Royal Opera House, and discuss how identity is created through a connection with opera and/or ballet in general and the Royal Opera House in particular. We then go on to explore how the strength of that connection and development of a shared identity can create a sense of symbolic immortality and influence the legacy giving decision, drawing on peak memorable experiences and nostalgia as a social emotion that connects people to what they love. We conclude by reflecting on how other non‐profits might create or stimulate such identities.